Primary leiomyosarcoma of kidney in a young adult - Pal, Dilip Kumar; Saraf, Siddharth; Mitra, Pubali; Ray, Suchandra (Indian Journal of Case Reports, 2018)
Primary renal leiomyosarcoma (LMS) is an extremely rare tumor constituting to